Assessing the sustainability content of the Nigerian engineering curriculum. Issue 4 (7th May 2019) - Akeel, Usman Umar; Bell, Sarah Jayne; Mitchell, John E.
Abstract : Purpose: The purpose of this study is to present an assessment of the sustainability content of the Nigerian engineering curriculum in universities. Design/methodology/approach: Content analysis is used to generate and analyse data from three engineering documents, namely, the Benchmark Minimum Academic Standards for Engineering Programmes in Nigeria and the engineering handbooks of two Nigerian higher education institutions. Findings: The Nigerian engineering curriculum is revealed to have a low sustainability content, with environmental concepts being the most cited themes and social topics as the least stated issues. Research limitations/implications: The sustainability assessment approach adopted in the study is constrained by the question of what constitutes a sustainability syllabus. Expert-derived sustainability themes used in the study are unavoidably incomplete and may limit the conduct of an exhaustive sustainability content assessment. Practical implications: Based on the research outcome, the Council for the Regulation of Engineering in Nigeria and other stakeholders can consider ways to adequately incorporate sustainability themes in the Nigerian engineering curriculum. Originality/value: The research is an effort to determine the presence of sustainability issues in the Nigerian engineering education, which has hitherto been scarcely documented. This study provides a baseline and a rationale for sustainability education interventions in the Nigerian engineering curriculum. It also presents a methodology for analysing sustainability content in university curriculum and contributes to the continuing sustainability education discourse, especially in relation to sub-Saharan Africa.